(untitled) (Journal of Bangladesh Institute of Planners, 2016)
The aim of this study is to explore the level of fire hazard risk associated with coexistence of chemical warehouses with residential units in Dhaka, the capital city of Bangladesh. The concept is to analyse fire hazard risk for such type of land use mix through a fire hazard risk index developed for this specific context. In the paper, the authors propose the construction of a fire hazard risk index for determining the risk level. The proposed index is applied to a study of fire hazard risk assessment of a high concentration chemical warehouse zone in the old parts of Dhaka. Consultation with several stakeholder groups in the study area and survey techniques were employed to assess the level of fire hazard risks. The results showed that fire hazard risk was a result of storing and handling flammable chemical products in mixed use buildings, the structural inefficiency of buildings for fire safety and a lack of awareness of the buildings’ users regarding fire safety rules and safe handling of chemical products. JBIP, Vol. 9, 2016 (Printed in April 2018), pp. 113-124